CORRELATIONS AND DIFFERENCES BETWEEN SHARIA, FIQH, AND USHUL FIQH - Nasikhah, Fatwai; Yahya, Muhamad Slamet (Jurnal Konseling Pendidikan Islam, 2026)
This study analyzes the relationship and fundamental differences between Shari’ah, Fiqh, and Usul al-Fiqh within the Islamic legal system. Shari’ah, etymologically meaning "the path to the water source," refers terminologically to the totality of Divine law revealed through the Qur’an and Sunnah. It is absolute, universal, and comprehensive, encompassing creed (aqidah), worship (ibadah), transactions (mu‘amalah), and ethics (akhlaq). Fiqh, derived from the root faqaha meaning "deep understanding," is the science of practical legal rulings of the Shari’ah, extracted from detailed evidences through ijtihad. Usul al-Fiqh is the methodology and set of principles for deriving Shari’ah rulings from their sources. The correlation among the three forms an epistemological hierarchy with a functional relationship: Shari’ah as the authoritative source with qat‘i (definitive) status, Usul al-Fiqh as the intermediary methodology, and Fiqh as the interpretive product with zanni (probabilistic) status. The main differences lie in terms of sources and authority, scope and focus, as well as temporality and adaptability. A proper understanding of these three concepts is essential for the development of Islamic law that remains responsive to contemporary challenges.